Shaping prestimulus neural activity with auditory rhythmic stimulation improves the temporal allocation of attention. Issue 7 (4th May 2016) - Ronconi, Luca; Pincham, Hannah L.; Cristoforetti, Giulia; Facoetti, Andrea; Szűcs, Dénes
Abstract : Human attention fluctuates across time, and even when stimuli have identical physical characteristics and the task demands are the same, relevant information is sometimes consciously perceived and at other times not. A typical example of this phenomenon is the attentional blink, where participants show a robust deficit in reporting the second of two targets (T2) in a rapid serial visual presentation (RSVP) stream. Previous electroencephalographical (EEG) studies showed that neural correlates of correct T2 report are not limited to the RSVP period, but extend before visual stimulation begins. In particular, reduced oscillatory neural activity in the alpha band (8-12 Hz) before the onset of the RSVP has been linked to lower T2 accuracy. We therefore examined whether auditory rhythmic stimuli presented at a rate of 10 Hz (within the alpha band) could increase oscillatory alpha-band activity and improve T2 performance in the attentional blink time window. Behaviourally, the auditory rhythmic stimulation worked to enhance T2 accuracy. This enhanced perception was associated with increases in the posterior T2-evoked N2 component of the event-related potentials and this effect was observed selectively at lag 3. Frontal and posterior oscillatory alpha-band activity was also enhanced during auditory stimulation in the pre-RSVP period and positively correlated with T2 accuracy. These findings suggest that ongoing fluctuations can be shaped by sensorial events to improve the allocation of attention in time. Abstract : Supplemental Digital Content is available in the text.